2022
DOI: 10.3389/fimmu.2022.790924
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Long Non-Coding RNAs in Ankylosing Spondylitis

Abstract: Ankylosing spondylitis (AS) is a chronic systemic autoimmune disease characterized by inflammation, bone erosion, spur formation of the spine and the sacroiliac joints. However, the etiology and molecular pathogenesis of AS remain largely unclear. Recently, a growing number of studies showed that long non-coding RNAs (lncRNAs) played critical roles in the development and progression of autoimmune and orthopedic conditions, including AS. Studies demonstrated that a myriad of lncRNAs (e.g. H19, MEG3, LOC645166) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…LINC00311, NKILA and Lnc-ITSN1-2 can be used to monitor the activity and assess the prognosis of AS. H19 and MEG3 are potential therapeutic targets for AS (Sun et al, 2022). In our study, 137 upregulated and 126 downregulated lncRNAs were found in ASMSCs during adipogenesis as compared to HDMSCs.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…LINC00311, NKILA and Lnc-ITSN1-2 can be used to monitor the activity and assess the prognosis of AS. H19 and MEG3 are potential therapeutic targets for AS (Sun et al, 2022). In our study, 137 upregulated and 126 downregulated lncRNAs were found in ASMSCs during adipogenesis as compared to HDMSCs.…”
Section: Discussionmentioning
confidence: 56%
“…Through interacting with DNA, RNAs and/or proteins, they play crucial roles in various cellular processes, including cell differentiation, the cell cycle and metabolism (Bridges et al, 2021). Evidence is accumulating that lncRNAs not only participate in the adipogenic differentiation of MSCs, but also contribute to the pathogenesis of AS (Sun et al, 2022). Based on these findings, it is reasonable for us to presume that the enhanced adipogenesis of ASMSCs may be related to abnormal lncRNA expression.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, miR-146a expression has been found to be upregulated in ectopic vs. eutopic endometrial tissues ( 138 ). Furthermore, miR-146a expression has been found to be upregulated in patients with AS, and to induce the expression of TNF-α, IL-6 and IL-1B ( 139 ), while the frequency of the G allele and GG genotype of the rs2910164 SNP of miR-146a was shown to be significantly higher in patients with AS compared to healthy controls ( 87 , 89 ). Previous research has demonstrated the potential role of miR-196b in the pathogenesis of endometriosis, by targeting proliferation, angiogenesis and apoptosis ( 140 ).…”
Section: Shared Genetic Polymorphisms and Biological Mechanismsmentioning
confidence: 99%
“…However, the molecular mechanisms underlying the pathogenesis and progression of AS remain unclear, and the clinical therapeutic management of AS is dissatisfying. Evidence shows that lncRNAs play a pivotal role in AS development ( 101 ). The expression of MALAT1 is up regulated in cartilage tissue and chondrocytes isolated from AS patients.…”
Section: The Roles Of Malat1 In Ankylosing Spondylitismentioning
confidence: 99%